2021
DOI: 10.3389/fmats.2021.638019
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Hyperthermia in the 400–1,100 kHz Frequency Range Using MIONs of Condensed Colloidal Nanocrystal Clusters

Abstract: In the current study, we explored the magnetic hyperthermia performance of condensed–clustered magnetic iron oxide nanoparticles (MIONs) in the range of 400 kHz to 1.1 MHz at low field amplitudes. The strong interparticle interactions, present in such systems, can influence the hyperthermia power produced by MIONs. Herein, the heat dependence, as an increasing function of frequency, with a fixed magnetic field strength of 3 mT is recorded, revealing a direct relationship between the two physical quantities and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Regarding iron oxide nanomaterials, the SAR values presented here are among the highest compared to the literature (Table S1, ESI†) in terms of magnetic field and frequency conditions and are comparable or even better than the iron oxide cubes, 50,75 rods, 20 tubes, rings/hollow, 49 multicores, 71 assemblies, 76,77 branched, 72 and cube assemblies, 23 which have been recently reported. Among them, some materials reveal extremely high SAR values, in the order of a few thousand W g −1 , but we have to notice, taking into consideration the linear dependence with the frequency 52,78 that this is mainly due to the very high frequency up to 700 kHz. In addition, it should be noted that these frequencies are much higher than the recommended frequency for human exposure (lower than 200 kHz).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding iron oxide nanomaterials, the SAR values presented here are among the highest compared to the literature (Table S1, ESI†) in terms of magnetic field and frequency conditions and are comparable or even better than the iron oxide cubes, 50,75 rods, 20 tubes, rings/hollow, 49 multicores, 71 assemblies, 76,77 branched, 72 and cube assemblies, 23 which have been recently reported. Among them, some materials reveal extremely high SAR values, in the order of a few thousand W g −1 , but we have to notice, taking into consideration the linear dependence with the frequency 52,78 that this is mainly due to the very high frequency up to 700 kHz. In addition, it should be noted that these frequencies are much higher than the recommended frequency for human exposure (lower than 200 kHz).…”
Section: Resultsmentioning
confidence: 99%
“…The frequency dependence on the produced power is almost linear in a wide frequency range. 52 However, there are limits of human exposure for both, with the recommended frequency proposed to be about 200 kHz or lower. 53 Selected data associated with the morphology and size effects combined with hyperthermia conditions (magnetic field and frequency) in relation to the SAR values, and therefore magnetic hyperthermia performance, are summarized in Table S1 in the ESI †…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen from the results, all SAR values were around 35 W/g Fe, and the maximum SAR value reached at 38.3 W/g Fe in 10 mg/mL of aqueous dispersion. The heating property indicated that it is anticipated to meet application requirements in hyperthermia with optimization of the core particle. Bao et al reported the size effect on the heating efficiency of PEG-modified Fe 3 O 4 NPs . Their results showed that the SAR values of the particles with mean sizes of 6 and 8 nm were 8.35 and 30.0 W/g Fe, respectively, at the conditions of 20.7 kA/m and 325 kHz.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, magnetic hyperthermia effects may be achieved through the application of weak magnetic fields (<7.95 kA/m) [ 3 ]; hence, relatively low magnetic fields were used for these Ca 2 Fe 2 O 5 microsphere induction heating studies. Furthermore, the field frequency (204 kHz) used was within the clinically accepted range for magnetic hyperthermia [ 3 , 30 , 50 , 51 , 52 , 53 , 54 , 55 ]. Additionally, in the present induction coil experiments the target temperature was achieved rapidly (~40 s), indicating that these microsphere products are promising candidates for reduced periods of magnetic hyperthermia exposure, thereby preventing and reducing patient discomfort [ 3 ].…”
Section: Discussionmentioning
confidence: 99%